Non-specific pain in the lumbar spine and the mobility of the hip joint in judokas - Štefanovsky, M.; Krisandova, A.; Kraeek, S.; Argajova, J.; Slizik, M. (Zdravotnícke listy, 2019)
Background: The hip joint is very often stressed and heavily loaded in the performance of diverse techniques in martial arts performance. Objective: The aim of our work was to verify the effect of chro-nic non-specific pain in the lumbar spine on the level of active and passive rotation of the hip joint in the group of high-level judokas. Sample and methods: A total of 17 judokas, including 9 males and 8 females, an average age of 18.65 ± 2.83 years, a body height of 171.18 ± 8.02 cm and a body weight of 64.06 ± 11.00 kg were divided into groups based on their anamnesis: group (n = 8) with lumbar spine pain for more than 6 months (nsLBP) and control group (n = 9) without pain (CG). Results: Based on the results of the research we did not find statistically significant differences in the active and passive hip intra- and extra-rotation between nsLBP and CG groups. How-ever, we found a moderate substantive significance between nsLBP and CG in the active and passive internal rotation of left lower limb, indicating a possible relationship between lumbar spine pain and reduced hip mobility. We also found a lower value for hip joint mobility in judo players compared to refe-rence values. Conclusion: The probands in both our groups showed a lower range of motion in the hip joint compared to the general popu-lation, therefore judo coaches need to pay more attention to the development of hip mobility.